Exploring the challenges and needs of nursing students in relation to OSCE exam stress: A qualitative study - Fahimeh Alsadat Hosseini; Mehrvash Hemati; Maryam Shaygan; Somayeh Gheysari; Azita Jaberi; Mojtaba Ghobadi; Shoeleh Rahimi (PLoS ONE, 2025)
Background The Objective Structured Clinical Examination (OSCE) is a critical assessment method in nursing education but is often associated with significant stress, negatively impacting students’ psychological well-being and academic performance. Understanding the sources of OSCE-related stress and effective coping strategies is crucial for improving nursing education. The aim of this study is to explore the challenges and needs of nursing students regarding OSCE stress. Methods Using content analysis, 18 participants (12 nursing students and 6 faculty members) from a nursing school in Shiraz, Iran, were interviewed through in-depth, semi-structured interviews. Data were analyzed using Graneheim and Lundman’s content analysis approach, ensuring rigor through Guba and Lincoln’s trustworthiness criteria. Results The analysis identified three main themes: ‘implementing OSCE stress management strategies,’ ‘enhancing OSCE education and assessment processes,’ and ‘preparing students for OSCE.’ These themes reflect the key challenges and effective factors influencing OSCE-related stress among nursing students. Conclusion There is a need for comprehensive interventions, including effective stress management strategies, improvements in OSCE training and evaluation methods, and structured preparation programs. Addressing these factors can alleviate OSCE-related stress and enhance student performance. Nursing educators and policymakers should integrate these insights to optimize OSCE implementation, ultimately fostering better psychological resilience and academic success among nursing students.